Trends in Assessment: Implications and Opportunities for Department Chairs - Stephen P Hundley (Academic Chairpersons Conference Proceedings, 2018)
Learn about trends in assessment from the executive editor of Assessment Update and chair of the national-level Assessment Institute. Attention will be paid to the role of the chair in creating a culture of assessment, supporting student success, and in using assessment results to inform department planning and improvement efforts.
Keywords: Assessment; trends; student success; planning; and improvement